Electrical properties of bisphenol-A-free magnetoactive borosilicate polymers - Xuyan Loo; Bhavana Nagaraju; Sai Pathivada; Alexander Bartsch; Thomas Schratzenstaller; Robert Sattler; Gareth J. Monkman (AIP Advances, 2024)
The recent REACH regulations require the elimination of bisphenol-A and titanium dioxide from commercially available boron-based polymers. This has led to changes in some of the mechanical characteristics, which strongly influence the properties of magnetoactive borosilicate polymers. This work delivers results on the electrical properties and discusses some implications for future research using bisphenol-A and titanium-dioxide-free substitutes.